Fracture properties of green wood formed within the forks of hazel (Corylus avellana L.) - Özden, Seray; Slater, Duncan; Ennos, Roland (Springer Science and Business Media LLC, 2017)
Forks are one of the important biomechanical structures in trees because of their potential vulnerability to splitting. Many researchers have investigated the strength and stiffness properties of tree forks, but very little is known about the toughening mechanism within tree forks. In this study, the specific fracture energy (Gf, Jm−2) of forks of hazel (Corylus avellana L.) was investigated in the RT (Radial-Tangential) and TR (Tangential-Radial) fracture systems using double-edge-notched tensile tests. Sample Gf values were measured at between the central apex of bifurcations, at the side apices of bifurcations, in the parent stems and in the two branches of forks. The fracture surfaces were analysed by Scanning Electron Microscopy (SEM), and the wood density was determined. Gf was found to be considerably greater at the central apex of a bifurcation than in other sampling locations. Surprisingly, Gf of TR was greater than Gf of RT at the central apex, while the other four locations showed greater Gf values in their RT fracture systems. The density of the central apex of bifurcations was found to be around 22% greater than elsewhere. In addition, it was shown that there was a more tortuous and interlocked wood grain formation at the central apex of bifurcations. The combination of higher density and tortuous grain structure provides reinforcement at the
Keywords: Ecology; Physiology; Forestry; Plant Science